HUBUNGAN HUKUM ANTARA BANK DENGAN AGEN LAKU PANDAI (BRANCHLESS BANKING) DALAM PELAKSANAAN PERANTARA KEUANGAN (FINANCIAL INTERMEDIARY) DIHUBUNGKAN DENGAN PRINSIP KEPERCAYAAN (FIDUCIARY PRINCIPLE) - Priadhi Harry Ramdhany (Aktualita : Jurnal Hukum, 2019)
Bank as a financial services institution monetary and funds for people who have trusted to save their money and other’s loan for some capital to operate their business. Otherwise there are many people in Indonesia do not having deposite or knowing financial services such; Loan for capital business. For example in Indonesia  financial services only reach 52% from population. There are many factors include low income, there are no social guarantee otherwise the Bank distance is to far. Branchless Banking is a disruptive innovation from financial services for outreach people commonly village to increased potential Bank for people to save their money, loan for capital business without worried about Bank distance. With Principle Agency Of Branchless Banking there are many Agent in other’s outreached places eccept village. BTPN Tbk Wow! In Village Ciampea Bogor City was one of the most Principle Agency Of Branchless Banking in Indonesia. Therefore there are Law was binding in application Principle Agency Of Branchless Banking between Bank and Agent. The research will be descriptive and analytical research and also use a juridicial and normative approachment method. The stages of the research consist of literature and field research. Juridicial and normative approachment focus on Legal Standing Between Bank and Principle Agency Of Branchless Banking and the field research is Bank BTPN Wow! As a Branchles Banking financial services in Village Ciampea, Bogor City. Based on the results of the research, Financial Inclusion based on Legal Standing Between Bank and Principle Agency Of Branchless Banking related to Rules Of Contract such; Good Faith, Personality, and Agreement. The term of Agreement means capability, responsibility, and liability which different between Bank and Agent. Implementation procedure Customer due diligence (CDD) harm to Agent cause breaking or Crime against law or contract between bank or customer or it is a right for custumer to binding the Agent to Court